Self-care capacity in older adults living in Morelia, Michoacán - Lozano-Zúñiga, María Magdalena (2022)
Objective: To determine the level of self-care in older adults who live in Morelia, Michoacán.  Method: This research had a quantitative, descriptive approach, with a non-experimental design and a cross section. The sample was selected for convenience and was made up of 100 older adults. Main Results: The main findings indicate that 42% have a high self-care capacity, 27% high, 19% regular, 8% low and only 4% very low.  General Conclusion: These days, despite the fact that there is a lot of information about the needs of the elderly, there are few interventions that do not remain a mere utopia. For this reason, it is essential to develop programs where this age group is attended from their spaces, emphasizing in the self-care requirements necessary to guarantee a quality of life. Also, giving a call to all the nurses is made to provide an adequate, optimal and personalized service.